Short-term hyperoxia-induced functional and morphological changes in rat hippocampus - Hencz, Alexandra Julia; Magony, Andor; Thomas, Chloe; Kovacs, Krisztina; Szilagyi, Gabor; Pal, Jozsef; Sik, Attila (Frontiers in Cellular Neuroscience, 2024)
Excess oxygen (O2) levels may have a stimulating effect, but in the long term, and at high concentrations of O2, it is harmful to the nervous system. The hippocampus is very sensitive to pathophysiological changes and altered O2 concentrations can interfere with hippocampus-dependent learning and memory functions. In this study, we investigated the hyperoxia-induced changes in the rat hippocampus to evaluate the short-term effect of mild and severe hyperoxia. Wistar male rats were randomly divided into control (21% O2), mild hyperoxia (30% O2), and severe hyperoxia groups (100% O2). The O2 exposure lasted for 60 min. Multi-channel silicon probes were used to study network oscillations and firing properties of hippocampal putative inhibitory and excitatory neurons. Neural damage was assessed using the Gallyas silver impregnation method. Mild hyperoxia (30% O2) led to the formation of moderate numbers of silver-impregnated “dark” neurons in the hippocampus. On the other hand, exposure to 100% O2 was associated with a significant increase in the number of “dark” neurons located mostly in the hilus. The peak frequency of the delta oscillation decreased significantly in both mild and severe hyperoxia in urethane anesthetized rats. Compared to normoxia, the firing activity of pyramidal neurons under hyperoxia increased while it was more heterogeneous in putative interneurons in the cornu ammonis area 1 (CA1) and area 3 (CA3). These results indicate that short-term hyperoxia can change the firing properties of hippocampal neurons and network oscillations and damage neurons. Therefore, the use of elevated O2 concentration inhalation in hospitals (i.e., COVID treatment and surgery) and in various non-medical scenarios (i.e., airplane emergency O2 masks, fire-fighters, and high altitude trekkers) must be used with extreme caution.